A synergistic effect of lithium titanate/pristine graphene composite with enhanced lithium storage capability. (20th October 2020) - Liu, Kun; Wang, Jia‐ao; Man, Jianzong; Zhao, Deqiang; Yang, Jie; Han, Haoxuan; Chen, Pengyu; Sun, Juncai
Summary: Ameliorating the electronic conductivity and lithium‐ion diffusion coefficient (DLi + ) of lithium titanate (Li4 Ti5 O12 ) electrode is of great significance for realizing high‐performance anode in lithium‐ion batteries. Herein, a synergistic combination of Li4 Ti5 O12 nanoparticles and highly conductive pristine graphene (PG) sheets was designed to obtain enhanced lithium storage performance through a simple hydrothermal method, in which the PG was modified with polyvinyl pyrrolidone. The surface modification of Li4 Ti5 O12 nanoparticles and PG was instrumental in improving the interaction between the two components, leading to the close attachment of Li4 Ti5 O12 nanoparticles and the PG. Mechanisms underlying the favorable effects of PG for Li4 Ti5 O12 were demonstrated by density functional theory calculations, illustrating that the introduction of PG significantly enhances the electronic conductivity of Li4 Ti5 O12 . Moreover, the synergistic effect of Li4 Ti5 O12 nanoparticles and PG endows the composite with high DLi + (7.99 × 10 −14 cm 2 /s) and electron conductive networks. Consequently, the as‐prepared Li4 Ti5 O12 /PG electrode manifests outstanding rate performance (133 mAh/g at 8 C) and remarkable cyclability (150.1 mAh/g at 0.5 C), better than pure Li4 Ti5 O12 electrode. Even after cycling 1000 times at 10 C, the Li4 Ti5 O12 /PG electrode yields a discharge capacity of 118.8 mAh/g with merely 0.006% capacity decay per cycle. Our study offers a versatile way for the synthesis of high‐performance Li4 Ti5 O12 ‐based composites. Abstract : The Li4 Ti5 O12 /PG (pristine graphene) composite was synthesized through a facile hydrothermal method, in which the PG was modified with polyvinyl pyrrolidone. The surface modification of Li4 Ti5 O12 nanoparticles and PG was advantageous for improving the interaction between them, leading to the close attachment of Li4 Ti5 O12 nanoparticles to the PG. The synergistic effect of Li4 Ti5 O12 nanoparticles and PG endows the composite with superior electrochemical performances.